Laser processing of multicrystalline silicon for texturization of solar cells - Dobrzanski, L A; Drygala, A (Journal of materials processing technology, 2007)
The subject of the present paper is to design the technique of laser texturization for solar cells made of multicrystalline silicon and improve understanding of the interaction between laser light and workpiece. We explore how different transverse modes influence laser surface treatment and examine some details related to laser multimodal operation. Since constant increase in global production of photovoltaic power can be observed the new technologies for manufacturing solar cells of improved efficiency are developed. One of the most important factors influencing cells performance is reflectivity of its front side. Consequently, new methods for efficient reduction of reflectance are searched. One of the crucial stages which is carried out to increase solar radiation absorption is surface texturization. It is brought under well control for solar cells made of monocrystalline silicon. However, from the market point of view the reduction of production costs has essential meaning. As a result, the market share of multicrystalline cells systematically grows since the base material is approximately twice cheaper compared to monocrystalline silicon. But on the other hand, texturization methods used for monocrystalline silicon are ineffective in the case of multicrystalline silicon. Thus, it seems to be very interesting to investigate new alternative methods for effective texturization of multicrystalline silicon. One of the promising technologies is laser processing which is the subject of present paper.